Agri-Nanotechnology: A prosperous Approach to Indian Agriculture - T. N. V. K. V. Prasad (International Journal of Economic Plants)
Among the much advancement in sciences, nanotechnology is being visualized as a rapidly evolving field that has potential to revolutionize agriculture and food systems and improve the condition of the farmer. According to the US Environmental Protection Agency, nanotechnology is defined as the science of understanding and control of matter at dimensions of roughly 1-100 nm, where unique physical and chemical properties make novel applications possible. Nanotechnology when applied as a tool, can address some of the world’s most critical sustainable development problems in the areas of water, energy, health, environment, agriculture, biodiversity and ecosystem management. Taking research in nanotechnology into agriculture and it’s allied sectors is based on evidence from research in the developed countries in promising areas of agriculture and food production systems. Studies in these countries over the past few years indicate that nanotechnology has the potential to advance agricultural productivity through genetic improvement of plants and animals, delivery of genes and drug molecules to specific sites at cellular levels in plants and animals and nano ray based gene technologies for gene expressions in plants and animals under stress conditions. Nanostructures can be implanted into plants and animals during growth and development to collect and transmit vital real time data such as growth rates and physiological activities that provides clues on performance, productivity and exposure to environmental, chemical and physical hazards.